Preparation method and application of HD type calcium-based flue gas desulfurizer

By preparing HD-type calcium-based flue gas desulfurizer and utilizing nanomaterials to improve surface properties and porosity, the problem of low desulfurization efficiency of calcium-based desulfurizers was solved, achieving efficient desulfurization and resource utilization of by-products, and meeting ultra-low emission standards.

CN119281087AInactive Publication Date: 2025-01-10YUEYANG HAIDA ENVIRONMENTAL PROTECTION TECHCO
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411479525.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing calcium-based desulfurizers have shortcomings in desulfurization efficiency and reaction rate, making it difficult to meet ultra-low emission standards, and the utilization rate of desulfurization by-products is low.

Method used

HD-type calcium-based flue gas desulfurizer is used, which is composed of light calcium carbonate, nano-Al2O3, nano-La2O3, carbonamide, calcium hydroxide, semi-coke-copper composite material and kaolin. By improving surface properties and porosity, increasing reaction porosity, and utilizing porous structure and oxygen defects to enhance transport and diffusion, it achieves efficient desulfurization.

Benefits of technology

The SO2 concentration in flue gas was reduced to below 10 mg/Nm3 and the dust concentration to less than 5 mg/Nm3, meeting the ultra-low emission standards. The desulfurization byproducts can be used as cement raw materials, reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281087A_ABST
    Figure CN119281087A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of an HD type calcium-based flue gas desulfurization agent. The HD type calcium-based flue gas desulfurization agent is prepared from the following components: 30 to 60 parts of light calcium carbonate, 0.1 to 2 parts of nano Al2O3, 0.1 to 2 parts of nano La2O3, 10 to 20 parts of carbamide, 50 to 100 parts of calcium hydroxide, 50 to 100 parts of a semicoke-copper composite material, 20 to 50 parts of kaolin, 0.2 to 4 parts of a pore forming agent and 1 to 5 parts of sodium carboxymethyl cellulose. The preparation method comprises the steps of raw material preparation, mixing, molding, aging and drying. According to the preparation method and application of the HD type calcium-based flue gas desulfurizer, the sulfur concentration of sulfur-containing gas in tail gas emission can be reduced to 10 mg / Nm < 3 > or below, the dust emission concentration is smaller than 5 mg / Nm < 3 >, the flue gas desulfurizer completely meets the ultra-low emission standard, desulfurization by-products can also be used as cement raw materials, and the cost is low. The HD type calcium-based flue gas desulfurizer is wide in temperature application range, and is particularly suitable for desulfurization of coke dry quenching diffused gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flue gas desulfurization, and in particular to a preparation method and application of a HD type calcium-based flue gas desulfurizer. Background Art

[0002] SO2 is one of the main pollutants in industrial flue gas. Its excessive emission can cause a series of environmental problems such as acid rain and haze. Studies have shown that when SO2 is oxidized in the air to form sulfate aerosols, its toxicity to human health will increase by more than 10 times. Therefore, how to reduce the SO2 content in industrial flue gas has become a research focus in various industries.

[0003] Calcium-based desulfurizers are mainly used in the process of flue gas desulfurization after coal combustion. Flue gas desulfurization can generally be divided into three categories: wet method, dry method and semi-dry method according to whether water is involved and the dry and wet state of the desulfurization products.

[0004] At present, the wet flue gas desulfurization method is the most mature and widely used among many flue gas desulfurization methods (such as the limestone-gypsum method). For example, patent CN109078476A discloses a wet desulfurization system and method using a double calcium-based desulfurizer. The desulfurization system disclosed in the patent includes an absorption tower, a circulating pump, and a slurry pool. The top of the absorption tower is provided with an absorption tower flue gas outlet, the middle side wall of the absorption tower is provided with an absorption tower flue gas inlet, the slurry pool is located at the bottom of the absorption tower, and a spray pipe is also provided in the absorption tower. A conveying pipeline is connected between the spray pipe and the slurry pool, a circulating pump is connected to the middle of the conveying pipeline, and a pH value adjustment system is also provided on one side of the conveying pipeline. The wet flue gas desulfurization method has the problems of large floor space, easy corrosion, scaling, and clogging of the equipment, and secondary pollution.

[0005] Compared with wet flue gas desulfurization, dry / semi-dry desulfurization processes (such as calcium injection in the furnace, post-furnace humidification activation method / cloud spray drying method) have the advantages of simple system, low investment cost, small footprint, no sewage generation, etc. The final solid product produced can be comprehensively utilized and is easy to handle, and has been used in industry to a certain extent. The use of calcium-based compounds such as calcium oxide and calcium hydroxide as desulfurizers has become a mainstream desulfurization technology. However, the desulfurization technology using calcium oxide compounds highlights some disadvantages: for example, the reaction rate of calcium oxide and sulfur dioxide is slow and the desulfurization efficiency is low; generally a long reaction time is required; and the reaction product of calcium oxide and sulfur dioxide has poor temperature resistance.

[0006] For example, patent CN116808798A discloses a calcium hydroxide-based flue gas desulfurizer, including the following components by weight: 100 parts of modified calcium hydroxide, 30-50 parts of coal ash slag, 20-40 parts of ceramsite crushed material, 5-10 parts of iron oxide, 2-8 parts of magnesium oxide, 5-8 parts of hydroxyapatite, and 5-10 parts of sodium bentonite. Patent CN117101400B discloses a calcium-based desulfurizer and its composition and preparation method. The calcium-based desulfurizer composition includes: a calcium-based composite raw material, an auxiliary agent 1, and an auxiliary agent 2, wherein: the calcium-based composite raw material is a product of mixed calcination of a calcium-based raw material and a catalytic oxidation component; the auxiliary agent 1 is an organic polymer; and the auxiliary agent 2 is a salt containing phosphorus.

[0007] However, the calcium-based desulfurizer used in the dry / semi-dry method has a high calcium-sulfur ratio (1.5-1.6 for the semi-dry method and 2.0-2.5 for the dry method), low desulfurization rate and absorbent utilization rate, which limits its further promotion.

[0008] Therefore, improving the desulfurization rate of absorbents, fully meeting the ultra-low emission standards of flue gas desulfurizers, and developing highly active desulfurizers have become the main research contents of the desulfurization process. Summary of the invention

[0009] In order to achieve the purpose of the invention, the present invention provides a preparation method and application of HD type calcium-based flue gas desulfurizer, which can not only reduce the sulfur concentration of sulfur-containing gas in tail gas emission to 10mg / Nm 3 Below, the dust emission concentration is less than 5mg / Nm 3 It is a flue gas desulfurizer that fully meets the ultra-low emission standards, and the desulfurization by-products can also be used as cement raw materials. The HD type calcium-based flue gas desulfurizer has a wide temperature adaptability range and is particularly suitable for the desulfurization of coking dry quenching exhaust gas.

[0010] To achieve the above object, the present invention provides the following technical solutions:

[0011] On the one hand, the present invention provides an HD type calcium-based flue gas desulfurizer, which includes the following components, measured by weight: 30 to 60 parts of light calcium carbonate, 0.1 to 2 parts of nano Al2O3, 0.1 to 2 parts of nano La2O3, 10 to 20 parts of carbonamide, 50 to 100 parts of calcium hydroxide, 50 to 100 parts of semi-coke-copper composite material, 20 to 50 parts of kaolin, 0.2 to 4 parts of pore-forming agent, and 1 to 5 parts of sodium carboxymethyl cellulose.

[0012] The addition of nano-Al2O3 and nano-La2O3 in the present invention can change the surface characteristics of the calcium-based desulfurizer and increase the porosity. Carbon amide reacts with SO2 in the flue gas to generate ammonium sulfate, and the ammonia generated by the reaction and the nitrogen oxides (NO x ) undergoes an ammonia oxidation reaction to produce nitrogen and water.

[0013] The semi-coke-copper composite material of the present invention has a porous structure, which provides great convenience for the diffusion and mass transfer of the gas phase in the pores. The composite structure and the rich oxygen defects synergistically enhance the S 2- transfer and diffusion, thereby achieving efficient and selective deep desulfurization.

[0014] Furthermore, the following components are included in parts by weight: 45 parts of light calcium carbonate, 1.5 parts of nano-Al2O3, 1.5 parts of nano-La2O3, 15 parts of carbonamide, 100 parts of calcium hydroxide, 50 parts of semi-coke-loaded copper-zinc composite material, 35 parts of kaolin, 2 parts of pore-forming agent, and 3 parts of sodium carboxymethyl cellulose.

[0015] Furthermore, the pore-forming agent includes one of starch, corn starch, sucrose, lactose, sodium carbonate and sodium bicarbonate.

[0016] In one aspect, the present invention provides a method for preparing a HD calcium-based flue gas desulfurizer, comprising the following steps:

[0017] Step 1, preparation of semi-coke-copper composite material: activating industrial semi-coke with nitric acid to obtain activated semi-coke, adding the activated semi-coke into copper nitrate solution, adding nitric acid solution, carrying out hydrothermal reaction in a high-pressure hydrothermal autoclave, washing, drying and calcining to obtain the semi-coke-copper composite material.

[0018] Step 2, raw material preparation: prepare the required raw materials, including light calcium carbonate, nano Al2O3, nano La2O3, carbonamide, calcium hydroxide, semi-coke-loaded copper-zinc composite material, kaolin, pore-forming agent, and sodium carboxymethyl cellulose.

[0019] Step 3: Mixing: After the mixture is stirred evenly, water is added to obtain a viscous mixed material;

[0020] Step 4: Shaping: Send the mixed materials into the extruder to extrude and shape;

[0021] Step 5: Aging: let the shaped material stand at room temperature;

[0022] Step 6: Drying: The aged material is roasted and then cooled to obtain a HD calcium-based flue gas desulfurizer.

[0023] In the present invention, the roasting temperature is 70-100° C., which avoids the gasification of carbon amide in the desulfurizing agent during the preparation process.

[0024] Furthermore, the nitric acid activation treatment process of the semi-coke in step 1 is to activate the 10-20 mesh semi-coke in a nitric acid solution at 50-70°C for 1-2 hours to remove impurities and ash, then wash and dry, transfer to a tubular furnace and perform calcination and pore expansion treatment at 650-750°C in a nitrogen atmosphere to obtain activated semi-coke. Furthermore, the calcination refers to calcination at 300-350°C for 1-3 hours in a nitrogen atmosphere.

[0025] Furthermore, in the step 1, the solid-liquid ratio of the active semi-coke to the copper nitrate solution is 1:(3-6), and the solid-liquid ratio of the active semi-coke to the nitric acid solution is 1:(1-2), the unit is g / mL; the concentration of the copper nitrate solution is 1.5-2.5M, preferably 2M; and the nitric acid solution is 35-45wt.%.

[0026] Furthermore, the hydrothermal reaction conditions in step 1 are 150-170° C. for 9 hours.

[0027] Furthermore, the raw materials in step three are put into a mixer and stirred at a speed of 500 to 800 rpm for 1 hour.

[0028] Furthermore, in step 4, the extruder extrude the material into long strips with a diameter of 100 to 150 mm.

[0029] Furthermore, the aging standing time is 1 to 3 hours, preferably 1 hour.

[0030] Furthermore, the calcination temperature in step 5 is 70-100° C. and the calcination time is 1-2 hours. The calcination allows the gas in the material to flow away, thereby keeping the pores unobstructed, such as for subsequent desulfurization.

[0031] Furthermore, the specific surface area of ​​the HD calcium-based flue gas desulfurizer is 50 m 2 / g~80m 2 / g, crushing strength is 80N / cm~100N / cm, bulk density is 0.7~0.8kg / m 3 The desulfurization efficiency is 90% to 99%.

[0032] On the one hand, the present invention provides an application of an HD calcium-based flue gas desulfurizer, and the specific process is as follows: the sulfur-containing gas is transported to a reactor equipped with an HD calcium-based flue gas desulfurizer, the pressure in the reactor is set to 0.1-0.2 MPa, and the temperature is 50-350°C. The sulfur content of the outlet gas is measured by a trace sulfur analyzer to ensure the penetration of sulfur capacity.

[0033] Furthermore, the sulfur-containing gas is less than 150 mg / m 3 When the reactor space velocity is 100~1000h -1 ; Sulfur gas greater than 150mg / m3 When the reactor space velocity is 100~400h -1 .

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1. High desulfurization accuracy: high desulfurization efficiency, which can reduce the sulfur dioxide content in the flue gas to 10mg / m 3 The following meet strict environmental protection requirements;

[0036] 2. Fast reaction speed: The desulfurizer reacts quickly with sulfur dioxide in the flue gas, has a high penetration sulfur capacity, and can effectively remove sulfur dioxide from the flue gas;

[0037] 3. High fine desulfurization capacity: The penetration sulfur capacity is more than 35%, which is much higher than the general desulfurization process;

[0038] 4. Wide temperature range: It can maintain high efficiency desulfurization effect without strict temperature control and has strong adaptability;

[0039] 5. Reduce secondary pollution: The desulfurizer can effectively reduce the sulfur oxide content in the flue gas, reducing the pollution of sulfur dioxide to the environment. At the same time, the waste can be recycled, reducing the waste of resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.

[0041] Figure 1 The flowchart of the preparation method of HD calcium-based flue gas desulfurizer in the present invention;

[0042] Figure 2 This is a flow chart of the application of the HD calcium-based flue gas desulfurizer in Example 1 of the present invention.

[0043] Figure 3 This is an electron microscope image of the HD calcium-based flue gas desulfurizer in Example 1 of the present invention. DETAILED DESCRIPTION

[0044] As used herein:

[0045] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0046] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0047] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0048] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0049] The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0050] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing the specific embodiments and are not intended to limit the present invention. In the embodiments, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0051] The technical solution of the present invention is further described in detail below in conjunction with specific implementation methods.

[0052] Embodiment 1:

[0053] The invention provides an HD type calcium-based flue gas desulfurizer, comprising the following components: 45 parts of light calcium carbonate, 1.5 parts of nano Al2O3, 1.5 parts of nano La2O3, 15 parts of carbonamide, 100 parts of calcium hydroxide, 50 parts of semi-coke-loaded copper-zinc composite material, 35 parts of kaolin, 2 parts of sodium bicarbonate and 3 parts of sodium carboxymethyl cellulose.

[0054] The present invention provides a method for preparing a HD calcium-based flue gas desulfurizer, comprising the following steps:

[0055] Step 1, preparation of semi-coke-copper composite material: nitric acid activation treatment of industrial semi-coke, activation treatment of 10-20 mesh semi-coke in 40wt.% nitric acid solution at 60°C for 1h, removal of impurity ash, then washing and drying, transfer to a tube furnace for calcination and pore expansion treatment at 700°C in a nitrogen atmosphere to obtain activated semi-coke. Add the activated semi-coke to 1.5M copper nitrate solution, add nitric acid solution, perform hydrothermal reaction in a high-pressure hydrothermal autoclave, wash, dry, and calcine at 300°C for 1h in a nitrogen atmosphere to obtain a semi-coke-copper composite material.

[0056] Step 2, raw material preparation: prepare the required raw materials, including 45 parts of light calcium carbonate, 1.5 parts of nano Al2O3, 1.5 parts of nano La2O3, 15 parts of carbonamide, 100 parts of calcium hydroxide, 50 parts of semi-coke-loaded copper-zinc composite material, 35 parts of kaolin, 2 parts of sodium bicarbonate, and 3 parts of sodium carboxymethyl cellulose;

[0057] Step 3, mixing: according to the weight ratio in step 2, put all the raw materials into a blender, stir at a speed of 550 rpm for 1 hour, and after mixing and stirring evenly, add water to obtain a viscous mixed material;

[0058] Step 4: Shaping: The mixed materials are fed into an extruder to be extruded into a long strip with a diameter of 120 mm;

[0059] Step 5: Aging: Let the molded material stand at room temperature for 1 hour;

[0060] Step 6: Drying: The aged material is calcined at 80°C and then cooled to obtain a specific surface area of ​​50m 2 / g, crushing strength is 80N / cm, bulk density is 0.7kg / m 3 , desulfurization efficiency is 90% HD type calcium-based flue gas desulfurizer.

[0061] Among them, in step 1, the solid-liquid ratio of the active semi-coke to the copper nitrate solution is 1:5, and the solid-liquid ratio of the active semi-coke to the nitric acid solution is 1:1, and the unit is g / mL.

[0062] On the one hand, the present invention provides an application of an HD calcium-based flue gas desulfurizer, and the specific process is as follows: the sulfur-containing gas is transported to a reactor equipped with an HD calcium-based flue gas desulfurizer, the pressure in the reactor is set to 0.13 MPa, the temperature is 80°C, and the sulfur content of the outlet gas is measured by a trace sulfur analyzer to ensure the penetration of sulfur capacity.

[0063] Specifically, the sulfur-containing gas is less than 150 mg / m 3 When the reactor space velocity is 100-1000h -1 ; Sulfur gas greater than 150mg / m 3 When the reactor space velocity is 100-400h -1 .

[0064] Embodiment 2:

[0065] The invention provides an HD type calcium-based flue gas desulfurizer, comprising the following components: 40 parts of light calcium carbonate, 1.5 parts of nano Al2O3, 1.5 parts of nano La2O3, 20 parts of carbonamide, 100 parts of calcium hydroxide, 50 parts of semi-coke-loaded copper-zinc composite material, 35 parts of kaolin, 2 parts of sodium bicarbonate and 3 parts of sodium carboxymethyl cellulose.

[0066] The present invention provides a method for preparing a HD calcium-based flue gas desulfurizer, comprising the following steps:

[0067] Step 1, preparation of semi-coke-copper composite material: nitric acid activation treatment of industrial semi-coke, activation treatment of 10-20 mesh semi-coke in 40wt.% nitric acid solution at 60°C for 1h, removal of impurity ash, then washing and drying, transfer to a tube furnace for calcination and pore expansion treatment at 700°C in a nitrogen atmosphere to obtain activated semi-coke. Add the activated semi-coke to 1.5M copper nitrate solution, add nitric acid solution, perform hydrothermal reaction in a high-pressure hydrothermal autoclave, wash, dry, and calcine at 300°C for 1h in a nitrogen atmosphere to obtain a semi-coke-copper composite material.

[0068] Step 2, raw material preparation: prepare the required raw materials, including 40 parts of light calcium carbonate, 1.5 parts of nano Al2O3, 1.5 parts of nano La2O3, 20 parts of carbonamide, 100 parts of calcium hydroxide, 50 parts of semi-coke-loaded copper-zinc composite material, 35 parts of kaolin, 2 parts of sodium bicarbonate, and 3 parts of sodium carboxymethyl cellulose.

[0069] Step 3, mixing: according to the weight ratio in step 2, put all the raw materials into a blender, stir at a speed of 550 rpm for 1 hour, and after mixing and stirring evenly, add water to obtain a viscous mixed material;

[0070] Step 4: Shaping: The mixed materials are fed into an extruder to be extruded into a long strip with a diameter of 120 mm;

[0071] Step 5: Aging: Let the molded material stand at room temperature for 1 hour;

[0072] Step 6: Drying: The aged material is roasted and then cooled to obtain a specific surface area of ​​60m 2 / g, crushing strength is 83N / cm, bulk density is 0.73kg / m 3 , desulfurization efficiency is 93% HD type calcium-based flue gas desulfurizer.

[0073] Among them, in step 1, the solid-liquid ratio of the active semi-coke to the copper nitrate solution is 1:5, and the solid-liquid ratio of the active semi-coke to the nitric acid solution is 1:1, and the unit is g / mL.

[0074] On the one hand, the present invention provides an application of an HD calcium-based flue gas desulfurizer, and the specific process is as follows: the sulfur-containing gas is transported to a reactor equipped with an HD calcium-based flue gas desulfurizer, the pressure in the reactor is set to 0.15MPa, the temperature is 190°C, and the sulfur content of the outlet gas is measured by a trace sulfur analyzer to ensure the penetration of sulfur capacity.

[0075] Specifically, the sulfur-containing gas is less than 150 mg / m 3 When the reactor space velocity is 100-1000h -1 ; Sulfur gas greater than 150mg / m 3 When the reactor space velocity is 100-400h -1 .

[0076] Example 3

[0077] The invention provides an HD type calcium-based flue gas desulfurizer, comprising the following components: 45 parts of light calcium carbonate, 1.5 parts of nano Al2O3, 1.5 parts of nano La2O3, 15 parts of carbonamide, 100 parts of calcium hydroxide, 50 parts of semi-coke-loaded copper-zinc composite material, 35 parts of kaolin, 2 parts of sodium bicarbonate and 3 parts of sodium carboxymethyl cellulose.

[0078] The present invention provides a method for preparing a HD calcium-based flue gas desulfurizer, comprising the following steps:

[0079] Step 1, preparation of semi-coke-copper composite material: nitric acid activation treatment of industrial semi-coke, activation treatment of 10-20 mesh semi-coke in 45wt.% nitric acid solution at 60°C for 1h, removal of impurity ash, then washing and drying, transfer to a tube furnace for calcination and pore expansion treatment at 700°C in a nitrogen atmosphere to obtain activated semi-coke. Add the activated semi-coke to 2M copper nitrate solution, add nitric acid solution, perform hydrothermal reaction in a high-pressure hydrothermal autoclave, wash, dry, and calcine at 320°C for 1h in a nitrogen atmosphere to obtain a semi-coke-copper composite material.

[0080] Step 2, raw material preparation: prepare the required raw materials, including 45 parts of light calcium carbonate, 1.5 parts of nano Al2O3, 1.5 parts of nano La2O3, 15 parts of carbonamide, 100 parts of calcium hydroxide, 50 parts of semi-coke-loaded copper-zinc composite material, 35 parts of kaolin, 2 parts of sodium bicarbonate, and 3 parts of sodium carboxymethyl cellulose;

[0081] Step 3, mixing: according to the weight ratio in step 2, put all the raw materials into a blender, stir at a speed of 550 rpm for 1 hour, and after mixing and stirring evenly, add water to obtain a viscous mixed material;

[0082] Step 4: Shaping: The mixed materials are fed into an extruder to be extruded into a long strip with a diameter of 120 mm;

[0083] Step 5: Aging: Let the molded material stand at room temperature for 1 hour;

[0084] Step 6: Drying: The aged material is roasted and then cooled to obtain a specific surface area of ​​65m 2 / g, crushing strength is 86N / cm, bulk density is 0.76kg / m 3 , desulfurization efficiency is 95% HD type calcium-based flue gas desulfurizer.

[0085] Among them, in step 1, the solid-liquid ratio of the active semi-coke to the copper nitrate solution is 1:5, and the solid-liquid ratio of the active semi-coke to the nitric acid solution is 1:1, and the unit is g / mL.

[0086] On the one hand, the present invention provides an application of an HD calcium-based flue gas desulfurizer, and the specific process is as follows: the sulfur-containing gas is transported to a reactor equipped with an HD calcium-based flue gas desulfurizer, the pressure in the reactor is set to 0.17 MPa, the temperature is 250°C, and the sulfur content of the outlet gas is measured by a trace sulfur analyzer to ensure the penetration of sulfur capacity.

[0087] Specifically, the sulfur-containing gas is less than 150 mg / m 3 When the reactor space velocity is 100-1000h -1 ; Sulfur gas greater than 150mg / m 3 When the reactor space velocity is 100-400h -1 .

[0088] Comparative Example 1

[0089] Compared with Example 1, the only difference is that a HD calcium-based flue gas desulfurizer does not contain nano-Al2O3 and nano-La2O3. Other operations and parameters are the same as those in Example 1.

[0090] Comparative Example 2

[0091] Compared with Example 1, the only difference is that a HD calcium-based flue gas desulfurizer and carbonamide are replaced by calcium hydroxide of the same mass. Other operations and parameters are the same as in Example 1.

[0092] Comparative Example 3

[0093] Compared with Example 1, the only difference is that an HD calcium-based flue gas desulfurizer and a semi-coke-loaded copper-zinc composite material are replaced with an equal mass of calcium hydroxide. Other operations and parameters are the same as in Example 1.

[0094] Activity Evaluation Example

[0095] Take 5g of the desulfurizers prepared in the above examples 1-3 and comparative examples 1-3, and conduct evaluation tests at room temperature (ambient temperature, usually -5°C to 45°C) and normal pressure (ambient pressure, usually 1 atmosphere) using standard gas containing 40000ppm of H2S. For qualitative detection, a self-prepared 1% silver nitrate solution can be used to detect the outlet sulfur; for quantitative detection, a domestically produced comprehensive microcoulomb meter can be used for detection, and the minimum detection amount of the instrument is 0.2ppm. The mechanical strength of the desulfurizer prepared in the above examples is determined by evaluating its compressive strength, wherein the average radial crushing force of the particles is determined according to the HG / T2782 standard. The test results are shown in Table 1.

[0096]

[0097] It can be seen from the above test results that the preparation method and application of the HD calcium-based flue gas desulfurizer provided by the present invention can achieve a sulfur capacity of more than 38%, a crushing resistance of more than 83%, and a desulfurization efficiency of more than 90% at normal temperature and pressure.

[0098] The preparation method and application of a HD calcium-based flue gas desulfurizer provided by the present invention have the advantages of high desulfurization accuracy, fast reaction speed, high fine desulfurization capacity, simple operation, no wastewater generation, ability to form general solid waste recovery, low cost, etc.

[0099] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. A HD type calcium-based flue gas desulfurizer, characterized in that: The invention comprises the following components in parts by weight: 30-60 parts of light calcium carbonate, 0.1-2 parts of nano-Al2O3, 0.1-2 parts of nano-La2O3, 10-20 parts of carbonamide, 50-100 parts of calcium hydroxide, 50-100 parts of semi-coke-copper composite material, 20-50 parts of kaolin, 0.2-4 parts of pore-forming agent and 1-5 parts of sodium carboxymethyl cellulose.

2. A method for preparing a HD calcium-based flue gas desulfurizer, characterized in that: The steps include: Step 1, preparation of semi-coke-copper composite material: activating industrial semi-coke with nitric acid to obtain activated semi-coke, adding the activated semi-coke into a copper nitrate solution, adding a nitric acid solution, performing a hydrothermal reaction in a high-pressure hydrothermal autoclave, washing, drying, and calcining to obtain a semi-coke-copper composite material; Step 2, raw material preparation: prepare the required raw materials, including light calcium carbonate, nano Al2O3, nano La2O3, carbonamide, modified calcium hydroxide, semi-coke-loaded copper-zinc composite material, kaolin, pore-forming agent, sodium carboxymethyl cellulose; Step 3: Mixing: After the mixture is stirred evenly, water is added to obtain a viscous mixed material; Step 4: Shaping: Send the mixed materials into the extruder to extrude and shape; Step 5: Aging: let the shaped material stand at room temperature; Step 6: Drying: The aged material is roasted and then cooled to obtain a HD calcium-based flue gas desulfurizer.

3. The preparation method according to claim 2, characterized in that: The pore-forming agent includes one of starch, corn starch, sucrose, lactose, sodium carbonate and sodium bicarbonate.

4. The preparation method according to claim 2, characterized in that: The nitric acid activation treatment process of the semi-coke in step 1 is to activate the 10-20 mesh semi-coke in a nitric acid solution at 50-70° C. for 1-2 hours to remove impurities and ash, then wash and dry it, and transfer it to a tubular furnace for calcination and pore expansion treatment at 650-750° C. in a nitrogen atmosphere to obtain activated semi-coke; further, the calcination refers to calcination at 300-350° C. in a nitrogen atmosphere for 1-3 hours.

5. The preparation method according to claim 2, characterized in that: In the step 1, the solid-liquid ratio of the active semi-coke to the copper nitrate solution is 1:(3-6), and the solid-liquid ratio of the active semi-coke to the nitric acid solution is 1:(1-2), the unit is g / mL; the concentration of the copper nitrate solution is 1.5-2.5M; and the nitric acid solution is 35-45wt.%.

6. The preparation method according to claim 2, characterized in that: The hydrothermal reaction conditions in step 1 are 150-170° C. for 9 hours.

7. The preparation method according to claim 2, characterized in that: The raw materials in step three are put into a mixer and stirred at a speed of 500-800 rpm for 1 hour; and the extruder in step four extrude the materials into long strips with a diameter of 100-150 mm.

8. The preparation method according to claim 2, characterized in that: The specific surface area of ​​the HD calcium-based flue gas desulfurizer is 50m 2 / g~80m 2 / g, crushing strength is 80, N / cm~100N / cm, bulk density is 0.7~0.8kg / m 3 The desulfurization efficiency is 90% to 99%.

9. An application of the HD calcium-based flue gas desulfurizer prepared by the method according to claim 2, characterized in that: The specific process is as follows: the sulfur-containing gas is transported to a reactor equipped with an HD calcium-based flue gas desulfurizer. The pressure in the reactor is set to 0.1-0.2 MPa and the temperature is 50-350°C. The sulfur content of the outlet gas is measured by a trace sulfur analyzer to ensure the penetration of sulfur capacity.

10. The use of the HD calcium-based flue gas desulfurizer according to claim 9, characterized in that: The sulfur-containing gas is less than 150 mg / m 3 When the reactor space velocity is 100~1000h -1 ; Sulfur gas greater than 150mg / m 3 When the reactor space velocity is 100~400h -1 .

Citation Information

Patent Citations

  • Modified calcium-based desulfurizing agent for dry desulfurization of sintering gas and preparation method of modified calcium-based desulfurizing agent

    CN103537177A

  • Sintering flue gas desulfurizer taking activated semi-coke as carrier and preparation and regeneration methods and application of sintering flue gas desulfurizer

    CN106179218A

  • Semidry desulfurization method for rotary kiln and desulfurizer

    CN107537308A

  • Deep purification fine desulfurizing agent and preparation method thereof

    CN110564457A

  • Calcium-based desulfurizing agent and preparation method thereof1

    CN112516780A